AMYAND HERNIA: A RARE SURGICAL VARIATION - Ahmed, Ghufran; Ashraf, Imran; Muazzam, Muhammad Ali; Shoaib, Muhammad; Shahid, Muhammad Farooq; Bukhari, Usman Shah (Pakistan Armed Forces Medical Journal, 2021)
Amyand’s hernia is an inguinal hernia with trapped appendix; its frequency is approximately 1%. Acute appendicitis is a rare clinical presentation (0.1%) of Amyand’s hernia. It was first described by Claudius Amyand in 1735. We report a patient of Amyand’s hernia, three years of age, presented with right inguinoscrotal hernia. Right side groin discomfort was present. Herniotomy was performed revealing anon-inflamed appendix within the inguinal canal for which a classic appendectomy was done.